Relation Between BMO and A2 Weight Functions - K.C., Durga Jang; Ghimire, Santosh (The Nepali Mathematical Sciences Report, 2016)
In this paper, we relate Bounded Mean Oscillation (BMO) function and A2 weight function. We show that logarithm of any A2 function is a BMO function and every BMO function is equal to a constant multiple of the logarithm of an A2 weight function. Moreover, we show that logarithm of any Ap weight function for 1 < p < ∞ is a BMO function.